(untitled) (Nigerian Journal of Health Sciences, 2025)
Background: Despite the continuous role of Personal Protective Equipment (PPE) in dental practice, most studies only focused on its use during the COVID-19 pandemic. Aim: This study therefore aimed to evaluate the prevalence and factors associated with compliance with PPE use after the COVID-19 pandemic. Materials and Methods: This cross-sectional study was conducted at the dental complex of the University of Benin Teaching Hospital, Benin City, Edo state from March to June 2022. All the staff of the dental section of the tertiary health facility were recruited for the study. A selfadministered questionnaire was used to collect both the sociodemographic and clinical data. The demographic data include age, sex, marital status, ethnicity, dental health workers, department, smoking, and alcohol intake. The clinical data consists of information on compliance with the use of PPE, history of previous exposure to COVID-19, presence of COVID-19 risk factor(s), availability of PPE, and availability of task force on the use of PPE. Both descriptive and inferential statistical analyses were performed. Results: The age range of the respondents was 18-70 years with a mean age of 37.3 ± 9.97 years. There were more (53.6%) female respondents than their male counterparts. A high proportion (69.6%) of the respondents were dental practitioners while the least (4.3%) respondents were the dental hygienist. More than two-thirds (92.8%) of the respondents said they comply with using PPE routinely when asked. Both the sociodemographic and clinical characteristics of the respondents were not significantly associated with the prevalence of compliance to the use of PPE (p>0.05) Conclusion: Our facility had a high prevalence of compliance with PPE use after the COVID-19 epidemic. However, no factors studied could influence the prevalence of compliance by oral health workers. How to cite this article: Amuh VO, Edetanlen BE. Prevalence and Factors Associated with Compliance to Personal Protective Equipment Use after COVID-19 2-year Post-pandemic among Oral Health Care Workers in a Nigerian Tertiary Hospital. Nigerian Journal of Health Sciences. 2024;24:60-65.